Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 13 - Cumulative Review: 17



Work Step by Step

$\frac{\frac{1}{z}-\frac{1}{2}}{\frac{1}{3}-\frac{z}{6}}$ $=\frac{\frac{2-z}{2z}}{\frac{2-z}{6}}$ $=\frac{2-z}{2z}\div\frac{2-z}{6}$ $=\frac{2-z}{2z}\times\frac{6}{2-z}$ $=\frac{6}{2z}$ $=\frac{3}{z}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.